Thyroxine Affects Lipopolysaccharide-Induced Macrophage Differentiation and Myocardial Cell Apoptosis via the NF-κB p65 Pathway Both In Vitro and In Vivo - Shan Zhu; Yuan Wang; Hongtao Liu; Wen Wei; Yi Tu; Chuang Chen; Junlong Song; Zhiliang Xu; Juanjuan Li; Changhua Wang; Shengrong Sun (Mediators of Inflammation)
Background. Numerous studies have demonstrated that the inflammatory response is involved in the progression of lipopolysaccharide- (LPS-) induced myocardial cell apoptosis. Accumulating evidence has shown that thyroxine participates in diseases by downregulating the inflammatory response. This study aimed at investigating whether thyroxine alleviates LPS-induced myocardial cell apoptosis. Methods. Bone marrow-derived macrophages (Mø) were treated with LPS and thyroxine, and Mø differentiation and Mø-related cytokine expression were measured. The effect of Mø differentiation on mouse cardiomyocyte (MCM) apoptosis was also detected in vitro. In addition, C57BL/6 mice underwent thyroidectomy and were treated with LPS 35 days later; subsequently, Mø differentiation and myocardial cell apoptosis in hearts were analyzed. To determine whether the nuclear factor-kappa B (NF-κB) p65 pathway mediates the effect of thyroxine on Mø differentiation and myocardial cell apoptosis, the specific NF-κB p65 pathway inhibitor JSH-23 was administered to mice that underwent a thyroidectomy. Results. Levothyroxine treatment significantly reduced the activation of the NF-κB p65 pathway, decreased M1 macrophage (Mø1) differentiation and Mø1-related cytokine mRNA levels in LPS-treated Mø, and increased M2 macrophage (Mø2) differentiation and Mø2-related cytokine mRNA expression. The protective effects of levothyroxine on MCM apoptosis mediated by LPS-treated Mø were alleviated by JSH-23. In mice, thyroidectomy aggravated LPS-induced cardiac injury and cardiac dysfunction, further promoted NF-κB p65 activation, and increased cardiac Mø1 expression and myocardial cell apoptosis but decreased cardiac Mø2 expression. JSH-23 treatment significantly ameliorated the thyroidectomy-induced increases in myocardial cell apoptosis and Mø differentiation. Conclusions. Thyroxine alleviated the Mø1/Mø2 imbalance, reduced the inflammatory response, decreased myocardial cell apoptosis, and protected against cardiac injury and cardiac dysfunction in LPS-treated mice. Thyroxine may be a novel therapeutic strategy to prevent and treat LPS-induced cardiac injury.